Comparison of Modified Biophysical Profile with Doppler Ultrasonographic Analysis in Determining Fetal well Being in the Third Trimester - Bakay, Kadir; Varolan, Ahmet; Yazgan, Ali; Akyol, Atif; Davas, İnci (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVES: In this study we aim to compare modified biophysical profile with Doppler ultrasonographic analysis in determining fetal well being in the third trimester. STUDY DESIGN: Our research is based on 99 voluntary pregnant patients ahead of 36 weeks who admitted to our hospital for labor between December 2009 and March 2010. Doppler ultrasonography and biophysical scoring were applied to all patients admitted to the study group. Following delivery, birth weight and APGAR scores of the 1st and 5th minute were noted down by the pediatrician. Prognosis and survey of all newborns admitted to the Neonatal Intensive Care Unit after delivery were closely monitored. The effectiveness of modified biophysical profile and obstetric Doppler analysis in determining the perinatal outcome was based on the evaluation of certain parameters such as; fetal distress, presence of meconium, admittance to NICU and APGAR score of the 5th minute. RESULTS: Our research is based on 99 voluntary pregnant patients between 18 and 40 years old and who are ahead of 36 weeks that were admitted to our hospital for labor between December 2009 and March 2010. Patients’ median age was 23.30±4.91, gravida changing between 1 and 5 with a median of 2 and parity changing between 0 and 2 with a median of 1. Birth weight measurements varied from 2680g to 3900g with a median of 3192.22±277.42 grams. Caesarean section was performed on 20 patients (20.2%). The remaining 79 (79.8%) were delivered vaginally CONCLUSION: Modified biophysical profile was found to be a more reliable tool than Doppler analysis in determining perinatal outcome and in prediction of acute fetal distress. But combining modified biophysical profile with Doppler analysis has yielded a higher sensitivity aiding in the diagnosis of perinatal outcome and acute fetal distress. In conclusion, in order to effectively predict acute fetal distress and to maintain a reliable screening method, combined use of these tests, namely modified biophysical profile and umbilical artery Doppler analysis, has proven to be the most valuable and effective method as shown in our study.